Things fall apart - Achebe, Chinua (New York : Distributed by Random House, 1992)
Set in an Ibo village in Nigeria, the novel recreates pre-Christian tribal life and shows how the coming of the white man led to the breaking up of the old ways.
"A Borzoi book"--T.p. verso.
Includes bibliographical references (p. xviii-xix).
Wilson's Senior High School.
Adult
Keywords: Historical fiction; Africa -- History -- Fiction; Nigeria -- History -- Fiction; Africa -- History -- Fiction; Nigeria -- History -- Fiction; Historical fiction